THE BALANCE OF MORAL KNOWING, MORAL FEELING, AND MORAL ACTION IN LANGUAGE LEARNING - Hindun Hindun (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
The purpose of this paper is to describe as clearly that moral knowledge is not enough to pass or taught course. Moral knowing (knowledge of moral) should continue to be guided or monitored its implementation phase (moral action= moral acts) in everyday life so that language learning is not just known learners but lived or felt (moral feeling= the feeling of moral) as the needs of the communication, as the needs of the communication, whether oral or in writing, so that any that exist in the minds of students could be realized in the form of a polite language and ultimately bring the dignity of this nation to the top of world civilization. As for the methodology that supports this article so that it is capable of being clearly descriptive shelled quantitative. Beginning of first language acquisition and second language, then the language learning in second language acquisition category became an important part of that would be seen side of coaching or development of his character to find out balance moral knowing, moral feeling and moral action. Next, the existence of this article may generate a response and a deep contemplation for anyone dabbling in the field of education in particular teacher or lecturer languages also observer languages.Contemplation is the character that's been reflected in any behavior or is it just in the concept or simply knowing only or new on the stage of knowing and feeling, but to implement them not enough time in the monitor so that the expected goal seems far away earth from sky. Keywords: moral knowing, moral feeling, moral action.